Manajemen Perubahan sebagai Moderasi pada Pengaruh Pair Programming terhadap Kemampuan Desain Logo Siswa DKV SMK Negeri 2 Magetan - Khoirul Roziqin; Yeni Anistyasari; Luthfiyah Nurlaela; Rommy Mochamad Ramdhani; I Gusti Putu Asto Buditjahjanto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This research was conducted to investigate whether the application of the Pair Programming influences the logo design competencies of students enrolled in vocational high schools (SMK), while also assessing the moderating Change Management as through the ADKAR framework. The study adopted a quasi-experimental methodology involving tenth-grade learners from the Visual Communication Design program at SMK Negeri 2 Magetan. Participants were allocated into two groups, consisting of an experimental cohort of 36 students and a control cohort of 108 students. To evaluate data, inferential statistics were applied, including Independent Sample t-test and Moderated Regression Analysis (MRA). Results showed no statistically meaningful difference in mean learning performance between students who engaged in collaborative learning and those who learned individually, as evidenced by a significance value of p = 0.9090. However, descriptive findings revealed that Pair Programming functioned as an effective safety net, maintaining the lowest student score at 57, slightly better than the individual method’s minimum of 56. Furthermore, the experimental group achieved a higher maximum score (97) compared to the control group (96). Regression analysis demonstrated that Change Management significantly moderates the effect of Pair Programming (p=0.001). The findings indicate a